Material Hardship and Association With Sexual Risk Behavior Among Adolescent Sexual Minority Males in 3 US Cities—National HIV Behavioral Surveillance—Young Men Who Have Sex With Men, 2015. (1st February 2022) - Trujillo, Lindsay; Robbins, Taylor; Morris, Elana; Sionean, Catlainn; Agnew-Brune, Christine
Abstract : Introduction: Adolescent sexual minority males (ASMMs) are disproportionately affected by HIV relative to other youth within the United States. Social determinants of health have been explored among this population; however, economic determinants, such as material hardship, remain understudied. We examined the relationship between material hardship and sexual behavior among ASMMs aged 13–18 years residing in 3 US cities using 2015 data from CDC's National HIV Behavioral Surveillance among Young Men Who Have Sex with Men. Methods: Young men ages 13–18 years residing in 3 US cities were recruited through venue-based, respondent-driven, or Facebook sampling. We estimated adjusted prevalence ratios (aPRs) with 95% confidence intervals (CIs) for condomless anal intercourse (CAI) with a male sex partner in the past 12 months and with having 4 or more male sex partners in the past 12 months. Results: Of 547 ASMMs, 27% reported experiencing material hardship in the past 12 months. After adjusting for demographics, household characteristics, and city, ASMMs who experienced material hardship were more likely to report CAI with a male partner in the past 12 months (aPR: 1.55, 95% CI: 1.25 to 1.93) and to have had 4 or more male sex partners in the past 12 months (aPR: 1.44, 95% CI: 1.08 to 1.91). Discussion: More than a quarter of ASMMs experienced material hardship that was associated with increased sexual risk behavior among ASMMs. Incorporating services that address all unmet needs is important to consider for HIV prevention efforts for ASMMs.